Stratigraphic Synthesis of the Danau Rayo Geosite: Possible Impact Fragmentation - Wijaya, Anton; Setiawan, Budhi; Rochmana, Yogie Zulkurnia (Universitas Negeri Gorontalo, 2026)
Lake Rayo in West Sulawesi, Indonesia, has been proposed as a potential meteorite impact structure, yet direct evidence supporting this origin remains limited. This study aims to provide a preliminary stratigraphic and granulometric characterization of Lake Rayo’s basin fill to clarify its genesis and support its geoheritage significance. Core sediment samples were collected from the basin floor and analyzed for grain size distribution, color (Munsell system), texture, and crack morphology using standard laboratory techniques. Seven stratigraphic intervals (BR1–BR7) were identified, showing clear vertical variations in granulometric parameters, sorting, and sediment color. Distinct fragmentation horizons, changes in color, and the occurrence of bedding cracks were interpreted as possible signatures of high-energy events, potentially associated with a meteorite impact. Comparative analysis with established impact structures, such as Lonar and Ries, revealed similar sedimentological features, supporting the impact hypothesis. These findings provide initial scientific evidence for the classification of Lake Rayo as an impact-related geoheritage site in Indonesia. The study also highlights the importance of integrating sedimentological data with future multidisciplinary research—such as geochemical and mineralogical shock analysis—to substantiate the impact origin more robustly. Overall, the results contribute valuable insights for geoheritage conservation, geoeducation, and the broader understanding of rare impact structures in Southeast Asia.